Prognostic Structural Neural Markers of MRI in Response to Mechanical Thrombectomy for Basilar Artery Occlusion - Liu, Chang; Song, Jia-Xin; Guo, Zhang-Bao; Chen, Lu-Ming; Zhao, Chen-Hao; Zi, Wen-Jie; Yang, Qing-Wu (Frontiers in Neurology, 2021)
OBJECTIVE: Mechanical thrombectomy (MT) has been the effective first-line therapeutic strategy for ischemic stroke. With impairments characteristics obviously separating from anterior circulation stroke, this research aimed to explore prognostic neural markers for basilar artery occlusion (BAO) after MT. METHODS: 54 BAO patients with multi-modal magnetic resonance imaging at admission from the multi-center real-world designed BASILAR research, were enrolled in this study. These features including volumes for cortical structures and subcortical regions, locations and volumes of infarctions, and white matter hyperintensity (WMH) volumes were attracted from all individuals. Impact features were identified after ANCOVA and logistic analysis. Another cohort (N=21) were further recruited to verify prognostic roles of screened prognostic structures. RESULTS: For the primary clinical outcome, decreased brainstem volume and total infarction volumes from mesocephalon and midbrain were significantly related to reduced 90-day mRS level after MT treatment. None of WMH volume, WMH grade, average cortex thickness, white matter volume and gray matter volume exhibited remarkable relationship with the prognosis of BAO. The increased left caudate volume was obviously associated with early symptomatic recovery after MT. The prognostic role of ratio of pons and midbrain infarcts volume in brainstem was further confirmed in another cohort with the AUC=0.78. CONCLUSIONS: This research was the first investigation to provide the comprehensive structural markers for the prognosis evaluation of BAO. The fully automatic and semi-automatic segmentation approaches in our study supported that the proportion of mesocephalon and midbrain infarcts volume in brainstem was the crucially prognostic structural neural marker for BAO.